2011
DOI: 10.3136/fstr.17.327
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins in Mesocarp/Epicarp and Endocarp of Fresh Acai (Euterpe oleracea Mart.) and their Antioxidant Activities and Bioavailability

Abstract: We measured anthocyanin levels in fresh açai (Euterpe oleracea Mart.), a native Amazonian palm fruit; cyanidin-3-O-glucoside (C3G) and cyanidin-3-O-rutinoside (C3R) in mesocarp/epicarp portion were 5.49 and 13.0 mg/g extracts, respectively, and these amounts were remarkably higher than that in endocarp. Hydrophilic ORAC assay suggested that açai mesocarp/epicarp extracts had potent antioxidant activity compared to blueberry extract. Following, absorption and excretion of açai anthocyanins were evaluated. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…The oxidative protective effects here described may be attributed to the presence of anthocyanins in AHE, predominantly cyanidin-3- O -rutoside and cyanidin-3- O -glucoside, as found by Jensen et al [ 36 ]. In fact, anthocyanins have been described as the main contributors for açaí antioxidant properties [ 7 , 12 , 26 , 40 , 41 ]. Açaí pulp extracts, rich in anthocyanins, also exhibit health beneficial properties (e.g., neuroprotective and cardioprotective) by mechanisms dependent on their antioxidant properties [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The oxidative protective effects here described may be attributed to the presence of anthocyanins in AHE, predominantly cyanidin-3- O -rutoside and cyanidin-3- O -glucoside, as found by Jensen et al [ 36 ]. In fact, anthocyanins have been described as the main contributors for açaí antioxidant properties [ 7 , 12 , 26 , 40 , 41 ]. Açaí pulp extracts, rich in anthocyanins, also exhibit health beneficial properties (e.g., neuroprotective and cardioprotective) by mechanisms dependent on their antioxidant properties [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pacheco-Palencia et al [ 29 ] states that extracts enriched with these compounds are responsible for antioxidant activity. Moreover, Agawa et al [ 30 ] and Poulose et al [ 31 ] reported the presence of the flavonoid quercetin and anthocyanins, such as cyanidin-3-glucoside and cyanidin-3-rutinoside ( Figure 1 and Table 1 ) in EO extracts, confirming their antioxidant activity. Poulose et al [ 31 ] also reported an anti-inflammatory effect, corroborating the results of Kang et al [ 32 ], Cedrim et al [ 33 ], and Mathias et al [ 34 ].…”
Section: Euterpe Oleracea Mart Plant Phytochemmentioning
confidence: 85%
“…Due to the EO fruit chemical composition, its application becomes desirable because of the high concentrations of metabolites responsible for significant antioxidant activity [ 30 , 31 , 36 , 39 ]. The patent BR 102017007451-0 A2 [ 108 ], published in 2018 ( Table 4 ), discloses the formulation of tablets, capsules, granulates and controlled-release pharmaceutical preparations from ethanolic EO extracts.…”
Section: Inventions Related To Eo As An Alternative Medicinementioning
confidence: 99%
“…The two glycosides were also detected in urine after 2 h from administration. However, there was no attempt to correlate bioavailability to in vivo antioxidant activity of the detected glycosides [ 89 ].…”
Section: Bioavailability Studies Of the Major Classes Of Natural Amentioning
confidence: 99%